Stem Cell Salvage of Injured Peripheral Nerve. Issue 2 (February 2015) - Grimoldi, Nadia; Colleoni, Federica; Tiberio, Francesca; Vetrano, Ignazio G.; Cappellari, Alberto; Costa, Antonella; Belicchi, Marzia; Razini, Paola; Giordano, Rosaria; Spagnoli, Diego; Pluderi, Mauro; Gatti, Stefano; et al.
We previously developed a collagen tube filled with autologous skin-derived stem cells (SDSCs) for bridging long rat sciatic nerve gaps. Here we present a case report describing a compassionate use of this graft for repairing the polyinjured motor and sensory nerves of the upper arms of a patient. Preclinical assessment was performed with collagen/SDSC implantation in rats after sectioning the sciatic nerve. For the patient, during the 3-year follow-up period, functional recovery of injured median and ulnar nerves was assessed by pinch gauge test and static two-point discrimination and touch test with monofilaments, along with electophysiological and MRI examinations. Preclinical experiments in rats revealed rescue of sciatic nerve and no side effects of patient-derived SDSC transplantation (30 and 180 days of treatment). In the patient treatment, motor and sensory functions of the median nerve demonstrated ongoing recovery postimplantation during the follow-up period. The results indicate that the collagen/SDSC artificial nerve graft could be used for surgical repair of larger defects in major lesions of peripheral nerves, increasing patient quality of life by saving the upper arms from amputation.